Asymptomatic anal sexually transmitted infections in HIV‐positive men attending anal cancer screening. (9th January 2016) - Fuchs, W.; Kreuter, A.; Hellmich, M.; Potthoff, A.; Swoboda, J.; Brockmeyer, N.H.; Wieland, U.
Summary: Background: HIV‐positive men who have sex with men (HIV+MSM) have an increased risk for anal dysplasia and for sexually transmitted infections (STIs). Objectives: We determined the positivity rates of Chlamydia trachomatis (CT), Neisseria gonorrhoea (NG), Mycoplasma genitalium (MG) and syphilis in HIV+MSM participating in an anal cancer screening programme. Methods: In total, 852 intra‐anal swabs were collected from 503 HIV+MSM between 2012 and 2014. Anal cytology and polymerase chain reaction assays for human papillomavirus (HPV), CT, NG and MG detection were performed. The syphilis status was determined serologically. Risk factors for STIs were explored by multiple logistic regression analysis. Results: In total 20·7% (104 of 503) of the patients had an STI other than HPV within the study period. The most common was CT, found in 10·9%, followed by NG (8·9%) and MG (4·2%). Early syphilis was detected in 4·6% and past syphilis in 44·5% of the HIV+MSM. Eighteen patients (3·6%) had more than one STI episode, and 90·6% of the 127 cases of STIs were asymptomatic. Age, anal HPV infection, abnormal anal cytology and previous syphilis were risk factors for STI. Conclusions: Anal STIs are frequent and mostly asymptomatic in HIV+MSM participating in anal cancer screening. STI screening should be incorporated into anal cancer screening programmes for HIV+MSM. Abstract : What's already known about this topic? HIV‐positive men who have sex with men (MSM) have an increased risk for anal dysplasia and anal cancer. Sexually transmitted infections are rising in MSM. What does this study add? Overall 21% of HIV‐positive MSM participating in an anal cancer screening programme had a curable sexually transmitted infection. Most of them (91%) were asymptomatic and would have been missed without targeted screening. Sexually transmitted infection screening should be incorporated into anal cancer screening programmes of high‐risk populations such as HIV‐positive MSM. Linked Comment: Spornraft-Ragaller and Beissert. Br J Dermatol 2016;174: 717–718 .